Análise do propósito negocial no planejamento tributário: conceitualização e sua função socioeconômica - Jacob, Camila Mosna Tomazella (2021)
This paper aims to deepen the analysis of the business purpose in tax planning operations, conceptualizing and evaluating it in light of its socioeconomic function. Therefore, the principles that are important and delimit the business purpose and tax planning operations are addressed. In the second part, the tax planning is conceptualized, verifying several institutes that are linked to this operation, conceptualizing such institutes and delimiting whether the link of these institutes to the tax planning makes sense. Furthermore, the limits to what is considered tax planning are established. In the third part, the business purpose is in evidence. The origin of the institute and its application in comparative law are presented. The two concepts of business purpose adopted are also presented. Article 116, sole paragraph of the National Tax Code, is analyzed and, finally, the link between tax efficiency and business purpose is verified, establishing its socioeconomic function